Pendampingan Penentuan Harga Jual Produk di UMKM Kieran Tea - Yuli Setiawannie; Andri Herlambang; Syahputra Amri (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This research was conducted to determine the cost of production of one of the micro, small and medium enterprises or UMKM that has the opportunity to sell individually packaged tea drinks. Meanwhile, in marketing Kieran tea products, several stages need to be carried out, especially in determining the price in the market before this tea product is put on the market, so that prices can be adjusted to compete in the market and at the same time be accepted by people who want to enjoy this special tea treat. In this research, the HPP method was used to determine the price that can be released to the market. After going through calculations, the selling price for camellia tea was obtained, namely IDR 12,300/bag and IDR 308,600/box. Business owners also understand the influence of the cost of production and expected profits in their business in determining the selling price of their products, so there is a significant difference between determining the selling price of products without taking HPP into account and those taking HPP into account.